Valuing Local Ownership - Refugees and Municipalities as Actors in the Search for Sustainable Solutions to Displacement - Bendel, Petra; Stürner, Janina (FAU University Press, 2019)
With the Global Compact on Refugees, the International Community seeks to highlight the importance of multi-stakeholder approaches in the search for sustainable solutions to displacement. However, when it comes to planning and implementing durable solutions, two of the main actors are often absent or even excluded from decision-making – these are refugees and hosting municipalities. The two papers in this publication highlight central bottlenecks for participatory approaches in both resettlement schemes as well as camp accommodation. Based on an analysis of existing good practice and new policy approaches, the first paper develops an innovative proposal for a Municipal Resettlement Programme while the second paper critically discusses potentials and risks of adapting special zones concepts to displacement contexts. Together, both papers are a call for action to actively engage refugees and communities so as to find answers to the question of “who could thrive where?”
Keywords: refugees; social integration; municipality; resettlement